Communication Patterns Of The Muslim Community Towards The Sapto Darmo Belief Community In Maintaining Religious Moderation In Wonokromo Village - Rizky Fika Mulia; Muhammad Hufron (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to find out how the communication patterns of the Muslim community with the Sapto Darmo belief community maintain religious moderation and what forms of harmony exist between the Muslim community and the Sapto Darmo belief community in Wonokromo Village. This research uses qualitative methods.   Data sources are obtained from primary data and secondary data. Methods for collecting data are interviews, documentation, and observation. The data obtained in the field was then made into field notes and a narrative of the research results. The narrative created is analyzed by data reduction, data presentation, and drawing conclusions.  The subjects of this research are the Muslim community and the Sapto Darmo faith community in Wonokromo Village, the object of this research is religious moderation. The results of the research show that the communication patterns of the Muslim community and the Sapto Darmo belief community in maintaining religious moderation in Wonokromo Village using the wheel communication pattern and the star communication pattern are working well. The Muslim community and Sapto Darmo in Wonokromo Village live in harmony and peace without any conflict between religious communities. Forms of religious moderation between the Muslim community and the Sapto Darmo belief community in Wonokromo Village are: 1) In cooperation activities, all communities take part, 2) Help each other when one of the groups needs help 3) Greet each other when they meet and often gather together